DEEP POLITICAL CRISIS IN THE REPUBLIC OF MADAGASCAR: STATEHOOD ON THE EDGE OF COLLAPSE - Andriamaharinjaka (RUDN Journal of Political Science, 2017)
The article is devoted to the political situation in the republic of Madagascar for the last few years. Current political processes in the republic are subjected to analysis. Special focus was made on the development of political crisis, the dependace of external and internal factors and their effects on political, economical and social situations in the country. The long-term consequences of the bad-organized parliamentary and presidential elections of 2013 are analyzed.